Constitutional Protection of Patient Privacy in the Digital Age during a Health Emergency - Aljazi, Jehad D.; Ehjelah, Abdullah; Mohammed Gassim Obeidat , Yusuf; Bahaaeddin M.S. Khwaira (Journal of Indonesian Constitutional Law, 2025)
This study aims to analyze the protection of patient privacy in the digital space in Jordan, focusing on the impact of social media on individuals' health data and assessing the adequacy of the current legislative framework. The study contributed to clarifying the scope of constitutional and legal protection of patients’ right to privacy in the relevant legislation against violations committed through social media platforms. It also analyzed the Defense Order on protecting the privacy of COVID-19 patients and highlighted the psychological impact of violating their privacy. This study employs a doctrinal legal research method that relies on a legislative and constitutional analysis approach to Jordanian privacy law. The results showed that privacy is no longer confined to traditional dimensions but has extended to the digital space, which represents an integral part of personal identity. The study also demonstrated that social media provides an environment vulnerable to health data violations, exposing patients to defamation and social stigma. Although Jordanian legislation provides constitutional protection for privacy, it lacks effective enforcement tools to address digital violations. This study concludes that developing a modern legislative system with clear controls over digital responsibility and raising legal and social awareness are crucial amid numerous violations of patients' constitutional right to privacy, especially during a health emergency. The study recommends that the legislature adopt more effective oversight, accountability, and remedial mechanisms when digital rights are violated, thereby enhancing the state’s ability to protect health privacy amid digital transformation.